Catalytic Dehydration of Ethanol over W/TiO2 Catalysts Having Different Phases of Titania Support - Pongsatorn Kerdnoi; Chaowat Autthanit; Nithinart Chitpong; Bunjerd Jongsomjit (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
This study aims to investigate the catalytic behaviors on W/TiO2 catalysts having different phases of TiO2 towards catalytic dehydration of ethanol to higher value products including ethylene, diethyl ether, and acetaldehyde. In fact, TiO2 support with different crystalline phases can result in differences of physico-chemical properties of the catalyst. Therefore, the present work reports on the catalytic behaviors that were altered with different phases of TiO2 in catalytic ethanol dehydration to diethyl ether or ethylene as a major product. To prepare the catalysts, three different phases [anatase (A), rutile (R), and mixed phases (P25)] of TiO2 supports were impregnated with 10 wt% of tungsten (W). It was found that the W/TiO2-P25 catalyst revealed higher activity among other catalysts. At 300 °C, all catalysts can produce the diethyl ether yield of 24.1%, 22.8%, and 10.6% for W/TiO2-P25, W/TiO2-A, and W/TiO2-R catalysts, respectively. However, when the reaction temperature was increased to 400°C, ethylene is the major product. The W/TiO2-P25 and W/TiO2-A catalysts render the ethylene yield of 60.3% and 46.2%, respectively, whereas only 15.9% is obtained from W/TiO2-R catalyst. The most important parameter influencing their catalytic properties appears to be the proper pore structure, acidity, and distribution of W species. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).